2015
DOI: 10.1039/c5cp05652g
|View full text |Cite
|
Sign up to set email alerts
|

Testing the transferability of a coarse-grained model to intrinsically disordered proteins

Abstract: The intermediate-resolution coarse-grained protein model PLUM [T. Bereau and M. Deserno, J. Chem. Phys., 2009, 130, 235106] is used to simulate small systems of intrinsically disordered proteins involved in biomineralisation. With minor adjustments to reduce bias toward stable secondary structure, the model generates conformational ensembles conforming to structural predictions from atomistic simulation. Without additional structural information as input, the model distinguishes regions of the chain by predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…After parametrization, it was demonstrated that the PLUM model folds several helical peptides, 14,23-26 stabilizes β-sheet structures, 14,15,[27][28][29] and is useful for probing the conformational variability of intrinsically disordered proteins. 30 We also considered two minor reparametrizations of the PLUM model: 1. The side chain van der Waals radius is decreased to 90% of its original value, 6 and 2.…”
Section: Plummentioning
confidence: 99%
“…After parametrization, it was demonstrated that the PLUM model folds several helical peptides, 14,23-26 stabilizes β-sheet structures, 14,15,[27][28][29] and is useful for probing the conformational variability of intrinsically disordered proteins. 30 We also considered two minor reparametrizations of the PLUM model: 1. The side chain van der Waals radius is decreased to 90% of its original value, 6 and 2.…”
Section: Plummentioning
confidence: 99%
“…The resulting data do not demonstrate any significant differences in the ensemble statistics of the two peptides when formed into oligomers. Structural differences reported previously [37] for the dimer do not persist into these larger aggregates. Conclusions regarding n16NN are somewhat more tentative than for n16N, as PLUM* data have not been validated against atomistic simulations for the mutant.…”
Section: Discussionmentioning
confidence: 67%
“…In the two-unit systems previously studied [37], a wholechain difference was seen in measures of conformational accessibility, including the frequency of interpeptide hydrogen bonds between n16N and n16NN, with the latter being higher. This led to the hypothesis that the whole-chain conformational accessibility, which may be a prerequisite of assembly, was compromised in the mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After parametrization, it was demonstrated that the PLUM model folds several helical peptides, 6,22-25 stabilizes βsheet structures, 6,[26][27][28][29] and is useful for probing the conformational variability of intrinsically disordered proteins. 30 We also considered 4 minor reparametrizations of the PLUM model:…”
Section: Plummentioning
confidence: 99%